Caracterização anatômica da madeira e potencial dendrocronológico de Schinopsis brasiliensis Eng. (Anacardiaceae) na caatinga sergipana - Cardoso, Danielle de Souza (2014)
The Schinopsis brasiliensis Engl. (braúna) is a long-lived species with wide distribution in phytogeographical areas of caatinga and cerrado. Due to uncontrolled exploitation of its timber and the environmental devastation of the caatinga is currently a threatened species. However, these trees have higher dimensions than other species of this environment and, therefore, have higher ecological importance. The biological and ecological characteristics of this species highlights the need of studies about theirs structures and reaction to environmental and climatic changes, among these wood anatomy and dendrochronology. The present study collected specimens of S. brasilienis from São Pedro Farm, in the municipality of Porto da Folha/SE. Living wood and construction wood samples were collected in June and July, 2013, through a non-destructive method, afterwards the samples were kept in the UFS Plant Anatomy and Dendroecology Laboratory, for sample preparations and data analisys. The heartwood and sapwood were significantly different in structure (p<0.05 for all analysis), which revealed that the structure of the heartwood is more resistant to environmental weathering, justifying its use for rural constructions in areas of caatinga. It has growth rings limited by marginal parenchyma band and/or thickness of the fiber walls; small vessels, and tyloses when in the heartwood; rays with procumbent and square cells that store many calcium oxalate crystals; and short and thick fibers. The cross-dating of growth rings series showed correlation of 0.52 between their live individuals and 0.49 among the construction wood. The chronology showed positive correlations with rainfall in the beginning and ending of the rainy season, and fall in the increase rate in the warmer and drier periods of the year, coinciding with the leaf fall and consequent disruption of metabolic activity in new xylem cells´ generation. The analysis of the rings in construction woods allowed new chronology expansion in Brazil, for the previous 20 years to the formation of the first growth ring of the older sample of S. brasiliensis.